1994
DOI: 10.1007/bf02036199
|View full text |Cite
|
Sign up to set email alerts
|

Pheromone chirality of african palm weevil,Rhynchophorus phoenicis (F.) and palmetto weevil,Rhynchophorus cruentatus (F.) (Coleoptera: Curculionidae)

Abstract: There are four stereoisomers of both 3-methyl-octan-4-ol, the aggregation pheromone of the African palm weevil,Rhynchophorus phoenicis (F.) and 5-methyl-octan-4-ol, the aggregation pheromone of the palmetto weevil,Rhynchophorus cruentatus (F.). Synthetic stereoisomers of 3-methyl-octan-4-ol and 5-methyl-octan-4-ol were baseline-separated on a Cyclodex-B fused silica column. Use of this column in gas chromatographic-electroantennographic detection (GC-EAD) and GC-mass spectrometric (GC-MS) analyses revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
4

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 47 publications
0
15
0
4
Order By: Relevance
“…There is a synergistic effect when these plant volatiles are combined with S,S-5-methyl-4-octanol (cruentol), the aggregation pheromone produced by R. cruentatus males (Weissling et al 1994a;Perez et al 1994). Large aggregations of male and female R. cruentatus are attracted to this combination, presumably for mating and oviposition purposes (Giblin-Davis et al 1994; Weissling et al 1993).…”
Section: Palms In the Landscape (Giblin-davis And Howard 1989) Recent mentioning
confidence: 97%
“…There is a synergistic effect when these plant volatiles are combined with S,S-5-methyl-4-octanol (cruentol), the aggregation pheromone produced by R. cruentatus males (Weissling et al 1994a;Perez et al 1994). Large aggregations of male and female R. cruentatus are attracted to this combination, presumably for mating and oviposition purposes (Giblin-Davis et al 1994; Weissling et al 1993).…”
Section: Palms In the Landscape (Giblin-davis And Howard 1989) Recent mentioning
confidence: 97%
“…A configuração absoluta desse composto foi determinada como (3S, 4S) (30b). 65,66 Testes de campo revelaram que o isômero (3S, 4S) foi mais ativo, mas que a presença do (3R, 4R) não prejudicou as capturas.…”
Section: Rhynchophorus Phoenicisunclassified
“…The inactivity of 5 may simply result from an insufficient release of the natural isomer. Gas chromatography showed that natural 5 was a pure diastereoisomer (Ramirez-Lucas et al, 1996), and probably a pure enantiomer as shown for all the rhynchophorinous pheromones investigated to date (Mori et al, 1993a, b;Oehlschlager et al, 1992;Perez et al, 1994;Phillips et al, 1989, Walgenbach et al, 1987. The presence of the regio-isomer 5-hydroxy-4-propyl-3-heptanone might also interfere with the perception of compound 5.…”
Section: Discussionmentioning
confidence: 87%